2015
DOI: 10.1063/1.4923428
|View full text |Cite
|
Sign up to set email alerts
|

Tunable plasmonically induced transparency with unsymmetrical graphene-ring resonators

Abstract: Articles you may be interested in Low-power, ultrafast, and dynamic all-optical tunable plasmonic analog to electromagnetically induced transparency in two resonators side-coupled with a waveguide system Plasmon-induced transparency in metamaterials: Active near field coupling between bright superconducting and dark metallic mode resonatorsThe multi-wavelength tunable plasmonically induced transparency (PIT) phenomena in two-ring and three-ring systems at infrared range were theoretically and numerically inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…Specifically, the chemical potential of graphene can be tuned via chemical doping or electrical gating [25, 26]. Mikhailov et al have experimentally shown that the carrier density in a graphene sheet as high as 10 14  cm −2 had been achieved, which led to a chemical potential of 1–2 eV at a temperature below 250 K [40].…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, the chemical potential of graphene can be tuned via chemical doping or electrical gating [25, 26]. Mikhailov et al have experimentally shown that the carrier density in a graphene sheet as high as 10 14  cm −2 had been achieved, which led to a chemical potential of 1–2 eV at a temperature below 250 K [40].…”
Section: Methodsmentioning
confidence: 99%
“…These remarkable and outstanding properties in turn enable a utility optical material in optoelectronic applications. In recent years, great attention has been focused on graphenebased plasmonic waveguides [23][24][25][26][27]. de Abajo et al have researched the propagation properties of graphene plasmonic waveguide constituted by individual and paired nanoribbons [28].…”
Section: Introductionmentioning
confidence: 99%
“…These remarkable and outstanding properties in turn enable a utility optical material in optoelectronic applications. In recent years, great attention has been focused on graphene-based plasmonic waveguides [ 23 27 ]. de Abajo et al have researched the propagation properties of graphene plasmonic waveguide constituted by individual and paired nanoribbons [ 28 ].…”
Section: Introductionmentioning
confidence: 99%